EFFECT OF SOIL TILLAGE SYSTEMS ON THE YIELD OF WHITE OATS (Avena sativa L.) - SANTOS, HENRIQUE PEREIRA (2001)
The adoption of soil tillage systems compatible with the soil, climate characteristics found in southern Brazil is an indispensable procedure for soil amendment and to maintain the commercial fields economically iMe- grated in the agricultura' production system. The effects of soil tillage systems on the yield of white oats (Avena saliva L.) were compared over a eight-year period in a crop rotation of wheat/soybean, commom vetch/corn, and white oats/soybean. Four soil tillage systems were evaluated: 1) no-tillage, 2) minimum tillage, 3) conventional ti Ilage using disk plow plus disk harrow, and 4) conventional tillage using moldboard plow plus disk harrow. An experimental design of blocks at random, with three replications were used. The main field plots (4 x 90 m) were formed by soil management systems, while the subplots (4 x 10 m) consisted of crop systems. The average yield of white oats grown under no-tillage from 1990 to 1997 (2,959 kg/ha) and under minimum tillage (2,938 kg/ha) was higher than the yield obtained for white oats grown under conventional tillage using either disk plow (2,709 kg/ha) or moldboard plows (2,682 kg/ha). Higher contents of soil organic matter, extractable P, and exchangeable K were ohserved in the 0-5 cm layer for the conservation tillage systems (minimum tillage and no-tillage), as compared to the conventional tillage systems (disk plow and moldboard plow). The no-tillage and minimum tillage system should be preferred for white oats cropping.